2022
DOI: 10.1093/braincomms/fcac223
|View full text |Cite
|
Sign up to set email alerts
|

Improving risk indexes for Alzheimer’s disease and related dementias for use in midlife

Abstract: Knowledge of a person’s risk for Alzheimer’s disease and related dementias (ADRDs) is required to triage candidates for preventive interventions, surveillance, and treatment trials. ADRD risk indexes exist for this purpose, but each includes only a subset of known risk factors. Information missing from published indexes could improve risk prediction. In the Dunedin Study of a population-representative New Zealand-based birth cohort followed to midlife (N = 938, 49.5% female), we compared associations of four l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…For example, it has been found that gray matter volume, a specific measure of brain health, partly mediates the longitudinal association between social isolation and cognitive function (Shen et al, 2022). Finally, we may speculate that there are implications for understanding dementia, a pathological form of cognitive dysfunction, given that a lack of social contact has been associated with elevated dementia risk (see reviews by: Desai, John, Stott, & Charlesworth, 2020; Kuiper et al, 2015; Penninkilampi, Casey, Singh, & Brodaty, 2018; Ren et al, 2023; and Sommerlad, Ruegger, Singh-Manoux, Lewis, & Livingston, 2018), and that older brain age has been considered to be a biomarker for (Gaser, Franke, Klöppel, Koutsouleris, & Sauer, 2013; Wang et al, 2019) and midlife antecedent of (Reuben et al, 2022) dementia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been found that gray matter volume, a specific measure of brain health, partly mediates the longitudinal association between social isolation and cognitive function (Shen et al, 2022). Finally, we may speculate that there are implications for understanding dementia, a pathological form of cognitive dysfunction, given that a lack of social contact has been associated with elevated dementia risk (see reviews by: Desai, John, Stott, & Charlesworth, 2020; Kuiper et al, 2015; Penninkilampi, Casey, Singh, & Brodaty, 2018; Ren et al, 2023; and Sommerlad, Ruegger, Singh-Manoux, Lewis, & Livingston, 2018), and that older brain age has been considered to be a biomarker for (Gaser, Franke, Klöppel, Koutsouleris, & Sauer, 2013; Wang et al, 2019) and midlife antecedent of (Reuben et al, 2022) dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Outcome Set 1: Dementia risk‐factor index included five indexes which are suitable for use in midlife (Supplementary Table S3): 3 The Cardiovascular Risk Factors, Aging, and Incidence of Dementia (CAIDE) index 28 ; The LIfestyle for BRAin health (LIBRA) index 29 ; The Australian National University Alzheimer's Disease Risk Index (ANU‐ADRI) 30 ; and Modifiable risk factors selected by the Lancet Commission on Dementia (Lancet) 31 ; and A comprehensive midlife index, the Dunedin ADRD Risk Benchmark (DunedinARB), comprised of 48 putative ADRD risk indicators organized into 10 conceptually distinct risk domains (Figure 1; Supplementary Table S4). 3 …”
Section: Methodsmentioning
confidence: 99%
“…Subjective Overall Health risk includes self, informant, and research‐worker ratings of Study member overall health. Figure from Reuben et al 3 . Details on the individual risk factors and indicators are provided in Supplementary Table 4.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations